2018
DOI: 10.2109/jcersj2.18036
|View full text |Cite
|
Sign up to set email alerts
|

Survey of new materials by solid state synthesis under external fields: high-pressure synthesis and microwave processing of inorganic materials

Abstract: The most common preparative method for inorganic solids is solid state reaction of constituent materials. Since the solid state reaction is usually performed at high temperature for a long heating duration, almost all the products are thermodynamically stable. During the long history of solid state chemistry and materials science, an enormous number of binary and ternary equilibrium phase diagrams were constructed and it seems like there is no hope to find out new materials those exhibit fascinating functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…erefore, scholars have conducted a lot of research studies on the numerical simulation of metal material's solid-state processing and have obtained many research results [8].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, scholars have conducted a lot of research studies on the numerical simulation of metal material's solid-state processing and have obtained many research results [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nonequilibrium reaction fields have the potential to synthesize functional materials with metastable phases and structures. 3) Furthermore, energy-efficient processes can be created by constructing synthetic pathways that can help address social issues such as carbon neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that NCL compounds may offer a unique platform to study the complex magnetic exchanges that favor intriguing topological spin textures. A very recent study on another high-pressure synthesized noncentrosymmetric ferromagnet Cr 4 Ge 7 suggested a defective disilicide-type structure and a T C of ∼270 K. However, the insufficient experimental data and analysis make an understanding of this intriguing phase obscure.…”
Section: Introductionmentioning
confidence: 99%